2018
DOI: 10.1093/abt/tby003
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab-mediated cardiotoxicity: current understanding, challenges, and frontiers

Abstract: Trastuzumab, an epidermal growth factor receptor 2 (HER2) targeting humanized monoclonal antibody, has been approved for the treatment HER2-positive breast cancer and HER2-positve metastatic gastric cancer. However, cardiotoxicity associated with its clinical application poses challenges for clinicians and patients, mechanisms of which are still evolving. This review will summarize the current mechanistic understanding of trastuzumab-mediated cardiotoxicity, discuss the novel role of DNA topoisomerase IIB as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 35 publications
3
92
0
3
Order By: Relevance
“…In line with this, Zardavas et al reported an increased risk of trastuzumabrelated cardiotoxicity (TRIC) in patients with increased cTn levels after anthracycline treatment [32]. This could be explained by the increased myocardial susceptibility to damage when the combination of anthracyclines and trastuzumab is being used [45,46]. On another hand, Kitayama et al reported elevated absolute hs-cTn levels throughout the treatment in patients developing CTAC, while baseline hs-cTn levels did not seem to have a significant predictive value [35].…”
Section: Cardiac Troponins Predictors Of Ctacmentioning
confidence: 84%
“…In line with this, Zardavas et al reported an increased risk of trastuzumabrelated cardiotoxicity (TRIC) in patients with increased cTn levels after anthracycline treatment [32]. This could be explained by the increased myocardial susceptibility to damage when the combination of anthracyclines and trastuzumab is being used [45,46]. On another hand, Kitayama et al reported elevated absolute hs-cTn levels throughout the treatment in patients developing CTAC, while baseline hs-cTn levels did not seem to have a significant predictive value [35].…”
Section: Cardiac Troponins Predictors Of Ctacmentioning
confidence: 84%
“…The incidence of New York Heart Association class III and IV cardiac dysfunction was also notably higher in patients who received trastuzumab with anthracycline and cyclophosphamide (16%) compared with those who received anthracycline and cyclophosphamide (3%), trastuzumab and paclitaxel (2%), or paclitaxel alone (1%) . Following the identification of trastuzumab‐associated cardiac events, subsequent trials of trastuzumab adopted stringent criteria for patient enrollment (excluding those at increased risk for cardiac adverse events), avoided concurrent use of trastuzumab with anthracyclines, implemented rigorous protocols for monitoring of cardiac function, and recommended discontinuation of trastuzumab upon detection of cardiac symptoms . In a retrospective analysis of women treated with HER2‐targeted therapy for metastatic breast cancer, most cases of symptomatic heart failure recovered with trastuzumab discontinuation and cardiac therapy .…”
Section: Resultsmentioning
confidence: 99%
“…One such compound that has improved breast cancer care is the human epidermal growth factor receptor 2 (HER2)‐targeted agent trastuzumab. Although trastuzumab can have cardiac‐associated side effects, effective monitoring and management have contributed to the success of this agent, highlighting the importance of cardiac monitoring in the successful treatment of patients with breast cancer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key side effect of trastuzumab is cardiotoxicity. 93 Throughout trastuzumab treatment, individuals in the PERSEPHONE trial were monitored for signs of cardiotoxicity based on their LVEF. Data on cause of death, including death as a result of chronic heart failure, were collected on a specific CRF that was filled in when required.…”
Section: Cardiac Toxicitymentioning
confidence: 99%